Pengaruh Motivasi Intrinsik dan Insentif terhadap Kinerja Pegawai pada PT Pos Indonesia (Persero) Kota Tangerang - Hindriari, Reni; Rosa, Tasya Fahriatur (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This research aims to examine the effect of intrinsic motivation and incentives on employee performance at PT Pos Indonesia (Persero) in Tangerang, both individually and simultaneously. Understanding these factors is crucial for organizations seeking to improve employee productivity and satisfaction. This study employs an associative method with a quantitative approach. The population consists of 56 employees, and a saturated sample technique was used, where all members of the population are included as samples. The analysis methods involve instrument testing, validity and reliability tests, classical assumption tests, and regression analysis, all using SPSS version 26. The research findings indicate that intrinsic motivation has a positive and significant impact on employee performance, suggesting that motivated employees perform better. Similarly, incentives also positively affect employee performance, reinforcing the importance of rewarding employees. When both intrinsic motivation and incentives are considered together, they show a substantial influence on performance. This implies that both individual and combined efforts of motivation and rewards are essential for improving employee productivity. The results emphasize the importance of a well-balanced motivational strategy and incentive system in enhancing employee performance, contributing to organizational success.